Studi Komparatif Literasi Sains Siswa Berdasarkan Gender dan Tempat Tinggal di MTs NU Jogoloyo - Ike Suryaningsih; Fenny Roshayanti; Endah Rita Sulistya Dewi (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to determine the achievement of scientific literacy skills in aspects of knowledge based on gender and place of residence. This study uses a quantitative descriptive method. The sample of this study was 60 seventh grade students at MTs NU Jogoloyo for the 2020/2021 academic year. The research instrument used was a test. Data analysis using total sampling technique. The results showed that the students' scientific literacy ability had an average in the low category, there was a significant difference in the average score based on gender and there was no significant difference in the average score based on place of residence.